Pengaruh Media Pembelajaran dalam Tataran Strategi Pembelajaran TPS (Think- Pair - Share) Terhadap Retensi Belajar Siswa SMA Mitra Inalum - Irwansyah Irwansyah (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This research was aimed to know The best learning strategy between the cooperative learning strategy type TPS with animation media, cooperative learning strategy type TPS with static picture media, and conventional learning strategy to the memory retency of XI grade students in State Senior High School Mitra Inalum. This research was conducted with quasi experiment methods with three classes which sample randomly, XI IA.1 class with cooperative learning strategy type TPS with animation media; XI IA. 2 class with , cooperative learning strategy type TPS with static picture media, and XI IA. 3 class with conventional learning strategy. Instrument in this research used achievement test in the form of 50 multiple-choice questions that have been tested for validity, reliability, dicrimination power, and difficulty level. Student’s retency memory can be gathered from the achievement test after 21 days sub matter is done finished. The techique of analysis used analysis of covarians with SPSS 17.0 for Windows. The result of this research and test shows the best learning strategy to get student memory retency is cooperative learning strategy type TPS with static picture media, continued by cooperative learning strategy type TPS with animation media, and then with conventional learning strategy. There are differences between memory retency XI grade students in State Senior High School of Mitra Inalum thay by used the cooperative learning strategy type TPS with animation media, cooperative learning strategy type TPS with static picture media, and conventional learning strategy (Sig.= 0.03 < 0.05).